(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the expanded parts of complex forms between morpheme level units, the changes that have occurred as a result of historical development. Although the expansion of complex forms is not common, it is a phenomenon that exists in the language. In the study, some of the expanded forms are analyzed and the discrepancies that occur in them are scientifically substantiated.